Investigation of Fish Species Diversity in the Shuhada River in Badakhshan Province, Afghanistan - Abdul Hallim Majidi; Mohammad Shoaib Shariati; Habibullah Hadafmand; Abdul Baser Qasimi (Turkish Journal of Bioscience and Collections)
Objective: The present research was conducted on the existence and species diversity of fish in the Shuhada River, one of the Kokcha River tributaries situated in Badakhshan Province, Afghanistan. There has not been a previous study on fish species diversity; this is the first attempt to fill out this gap and identify the fish species of the river. Materials and Methods: Fish specimens were collected from three selected sites in the Shuhada River. The study was performed twice in each season of the year 2022, by using a variety of fishing nets, like gill nets with a length of 5 m and a height of 2 m, although with meshes ranging from 3 to 3 cm knot to knot and hooks. Two samples were taken from each site in each season. Results: Generally, 463 fish specimens were collected from the three selected zones. The Futtah was one of the selected zones that had the highest number of fish species (38.8%), followed by Yasich (34.04%), and the least number of fish species (28.07%) were collected from the Maidan zone. It found that Salmo trutta is the most abundant species at 52.9%, followed by Schizothorax curvifrons at 34.5% and Paracobitis longicauda at 12.5% was the least abundant species. During the cold seasons of autumn and winter, fish migrate down in the Kokcha River, and in spring and summer migrate to the upper zone in cold water. Conclusion: During the current study, three fish species, Salmo trutta, Schizothorax curvifrons, and Paracobitis longicauda, were documented in the study area. Fish hunting and flooding are the main harmful forces causing the reduction of fish diversity in the Shuhada River.